PERENCANAAN RUANG DALAM DAN PELAKSANAAN PEMBANGUNAN MASJID JAMI AT-TAUFIQ TANJUNG GEDONG - Solikhah, Nafiah (Jurnal Bakti Masyarakat Indonesia, 2023)
The Jami At-Taufiq Mosque is located in Tanjung Gedong Village, Tomang Village, Grogol District, precisely on theeast side of Tarumanagara University (Untar) Campus I at a distance of 500 meters which is used by residents forreligious activities and social education. The Jami At Taufiq Mosque was chosen as the location for the CommunityService (PKM) partner based on the consideration of its location not being too far from Untar so that this PKMactivity could benefit the community around the Untar campus and be more ef ective in implementation andsupervision. There are two problems faced by partners. First, the limiting element of internal space is structuraldegradation, especially at the roof junction point. Second, the elements that fill the interior space are a result of theproblematic elements that divide the interior space, so that the interior space of the At Taufiq mosque cannot beutilized for activities optimally. The solution given to the problem of outdoor space dividing elements is by providingtechnical design and implementation proposals for the roof meeting area so that it is responsive to the flow ofrainwater and filling the interior space elements by applying Islamic planning, namely separating men's andwomen's areas in the form of partitions with geometric pattern elements. . The activity stages include: identifyinginternal space problems, preparing draft interior space planning drawings, determining implementation prioritiesas design realization, and stages of implementing design realization according to priorities. Based on the results ofthe activity, it is known that the elements dividing the interior space at the At Taufiq Mosque in the form of structuraldegradation, especially at the roof junction point, are the main problems that have been resolved by designing andrealizing renovations that take into account the roof elevation. PKM activities also produced furniture designproposals to optimize activities in the space inside the At-Taufiq Mosque. ABSTRAK: Masjid Jami At-Taufiq terletak di Kampung Tanjung Gedong, Kelurahan Tomang, Kecamatan Grogol, tepatnya disisi timur Universitas Tarumanagara (Untar) Kampus I dengan jarak 500 meter yang dimanfaatkan oleh wargauntuk aktivitas keagamaan maupun edukasi sosial kemasyarakatan. Masjid Jami At Taufiq dipilih sebagai lokasimitra Pengabdian kepada Masyarakat (PKM) berdasarkan pertimbangan lokasinya yang tidak terlalu jauh dariUntar sehingga kegiatan PKM ini bisa bermanfaat bagi lingkungan masyarakat sekitar kampus Untar dan menjadilebih efektif dalam pelaksanaan dan pengawasan. Terdapat dua permasalahan yang dihadapi oleh mitra. Pertama,elemen pembatas ruang dalam berupa degradasi struktur terutama pada titik temu atap. Kedua, elemen pengisiruang dalam sebagai dampak dari elemen pembatas ruang dalam yang bermasalah, sehingga ruang dalam padamasjid At Taufiq tidak bisa dimanfaatkan untuk aktivitas secara optimal. Solusi yang diberikan pada permasalahanelemen pembatas ruang luar yaitu dengan memberikan usulan desain teknis dan pelaksanaan pada area pertemuanatap agar responsif terhadap aliran air hujan dan pengisian elemen ruang dalam dengan menerapkan Islamicplanning yaitu pemisahan area laki-laki dan perempuan berupa partisi dengan elemen pola geometris. Tahapankegiatan meliputi: identifikasi masalah ruang dalam, penyusunan draft gambar perencanaan ruang dalam,penentuan prioritas pelaksanaan sebagai realisasi desain, dan tahapan pelaksanaan realisasi desain sesuaiprioritas. Berdasarkan hasil kegiatan, diketahui bahwa elemen pembatas ruang dalam pada Masjid At Taufiqberupa degradasi struktur terutama pada titik temu atap merupakan permasalahan utama yang telah diselesaikandengan desain dan realisasi renovasi yang mempertimbangkan elevasi atap. Kegiatan PKM juga menghasilkanusulan desain furniture untuk mengoptimalkan kegiatan di ruang dalam Masjid At-Taufiq.